2010
DOI: 10.1021/jm901830p
|View full text |Cite
|
Sign up to set email alerts
|

Bis(morpholino-1,3,5-triazine) Derivatives: Potent Adenosine 5′-Triphosphate Competitive Phosphatidylinositol-3-kinase/Mammalian Target of Rapamycin Inhibitors: Discovery of Compound 26 (PKI-587), a Highly Efficacious Dual Inhibitor

Abstract: The PI3K/Akt signaling pathway is a key pathway in cell proliferation, growth, survival, protein synthesis, and glucose metabolism. It has been recognized recently that inhibiting this pathway might provide a viable therapy for cancer. A series of bis(morpholino-1,3,5-triazine) derivatives were prepared and optimized to provide the highly efficacious PI3K/mTOR inhibitor 1-(4-{[4-(dimethylamino)piperidin-1-yl]carbonyl}phenyl)-3-[4-(4,6-dimorpholin-4-yl-1,3,5-triazin-2-yl)phenyl]urea 26 (PKI-587). Compound 26 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(103 citation statements)
references
References 31 publications
(66 reference statements)
2
101
0
Order By: Relevance
“…PKI-587 has a similar in vitro and in vivo profile to PKI-402. PKI-587 has broad in vivo efficacy in the MDA-MB-361, BT474, H1975, U87MG, and HCT116 tumor models [78] . PKI-587 has shown great potency against EGFR-and HER2-inhibitorresistant lung tumors.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%
“…PKI-587 has a similar in vitro and in vivo profile to PKI-402. PKI-587 has broad in vivo efficacy in the MDA-MB-361, BT474, H1975, U87MG, and HCT116 tumor models [78] . PKI-587 has shown great potency against EGFR-and HER2-inhibitorresistant lung tumors.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%
“…Serial samples (n ϭ 10) of blood (300 l) were taken at time points 0,2,10,15,30,60,120,240,360, and 1440 min after dosing via the Metabolite M1 and M1a-1 were shown to be identical by chiral HPLC . For description of the pharmacological assays, please see Venkatesan et al (2010 …”
Section: Methodsmentioning
confidence: 99%
“…Dual PI3K/mTOR inhibitor 25 ( Figure 7) showed inhibition of mTOR substrate 4EBP1 phosphorylation in a Lantha-Screen enzyme test (IC 50 =97 nM), it also showed moderately inhibition of downstream 4EBP1 phosphorylation and mTORC2 downstream AKT phosphorylation in two U-87 cellular assays [11]. PKI-587(PF-05212384, 26) ( Figure 7) is a dual PI3K-mTOR inhibitor (PI3Kα, PI3Kγ and mTOR, IC 50 values of 0.4, 5.4 and 1.6 nM, respectively) emerged recently possessing highly similar structure to previously known PI3K-mTOR dual inhibitor PKI-402 ( Figure 7) (PI3Kα, PI3Kγ and mTOR, IC 50 values of 1.4, 9.2 and 1.7 nM, respectively) with a triazolopyrimidine scaffold [14].…”
Section: 3 5-triazine Derivatives Targeting Both Pi3k and Mtormentioning
confidence: 98%
“…(2)The polarity of the whole molecule can be inherently imparted by three nitrogens presented at the 1, 3, 5-triazine core, and the designed compounds' clogP values can be lower. (3) Amide functionality with water stabilizing groups improved potency both in enzyme and in cell proliferation assays [11]. It has been extensively reported that the presence of sulfonamide, morpholine, or pyrimidyl moieties at 2, 4 or 6-positions of the 1, 3, 5-triazine core enhanced antitumor activity.…”
Section: Introductionmentioning
confidence: 99%